ABCB1 and CYP2D6 polymorphisms and treatment response of psychotic patients in a naturalistic setting. (18th December 2017) - Papazisis, Georgios; Goulas, Antonios; Sarrigiannidis, Alexios; Bargiota, Stavroula; Antoniadis, Diomidis; Raikos, Nikolaos; Basgiouraki, Emmanouela; Bozikas, Vasileios P.; Garyfallos, Georgios
Abstract: Objectives: The aim of our study was to examine the association between ABCB1 polymorphisms G2677T/A (rs2032582) and C3435T (rs1045642) and common CYP2D6 variants, with the response to antipsychotic treatment of psychotic patients, in a naturalistic setting, in Greece. Methods: One hundred patients suffering from schizophrenia and other psychotic disorders were included in the study. Dosages were normalized to chlorpromazine equivalents. Response following 1 month of treatment was assessed as either a continuous variable, using the distribution of the corrected Positive and Negative Syndrome Scale percent change, or as a dichotomous variable defined as the number of patients scoring ≥30% from the corrected baseline Positive and Negative Syndrome Scale score. Genotyping was achieved with established polymerase chain reaction–restriction fragment length polymorphism methods. Results: With response treated as a continuous variable, the homozygous recessive rs2032582 genotypes (TT) who were simultaneously carriers of a loss‐of‐function CYP2D6 allele (*4 or *5) responded significantly worse than the rest of the patients. Comparison of genotype frequencies revealed a statistically significant association of the above combination. No significant association between chlorpromazine equivalents and the tested genotypes was detected. Conclusion: We have detected a possible interaction between ABCB1 and CYP2D6 in affecting response of psychotic patients to drug treatment, in a naturalistic setting.